2021
DOI: 10.1097/tp.0000000000003654
|View full text |Cite
|
Sign up to set email alerts
|

Safety of the First Dose of SARS-CoV-2 Vaccination in Solid Organ Transplant Recipients

Abstract: Severe: prevents daily activity. d More than baseline. SARS-CoV-2, severe acute respiratory syndrome coronavirus 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
61
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 5 publications
11
61
1
1
Order By: Relevance
“…Of note, a recent study into COVID-19 vaccine response in 187 solid organ transplant recipients-half of whom had the BNT162b2 vaccine-did not report any episodes of acute rejection. 23 Little is known about the biodistribution of lipid nanoparticles, a factor which may be relevant in the two patients reported since tissue trafficking of the mRNA would determine whether the cells and tissues in the eye are killed by cytotoxic T cells. Given the rapid uptake of vaccine proteins throughout the body, it would be anticipated that any significant upregulation of the immune response due to RNA-driven protein expression would occur within the first weeks, as seen in published data from completed trials, allowing us to promptly identify if rejection might occur at increased rates after vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, a recent study into COVID-19 vaccine response in 187 solid organ transplant recipients-half of whom had the BNT162b2 vaccine-did not report any episodes of acute rejection. 23 Little is known about the biodistribution of lipid nanoparticles, a factor which may be relevant in the two patients reported since tissue trafficking of the mRNA would determine whether the cells and tissues in the eye are killed by cytotoxic T cells. Given the rapid uptake of vaccine proteins throughout the body, it would be anticipated that any significant upregulation of the immune response due to RNA-driven protein expression would occur within the first weeks, as seen in published data from completed trials, allowing us to promptly identify if rejection might occur at increased rates after vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of systemic events was slightly higher than reported in solid organ transplant recipients on immunosuppression who underwent early vaccination. 5 Strengths of this study includea national sample and novel, early data to inform major concerns among patients and their providers. Limitations include a relatively small, non-randomised sample, lack of longer-term safety data and a less granular ascertainment of side effects than the original trials.…”
mentioning
confidence: 99%
“…Happily, as more transplant patients went on to be vaccinated, early theoretical concerns of activation of the immune system by the vaccine, triggering episodes of rejection, have not been observed. 4 Thankfully, I got my tests done 1 month after the second dose of the vaccine, and all was good with my kidney transplant. However, questions still remain about the efficacy of the vaccine in immunosuppressed patients like me.…”
Section: Covid-19 Vaccines In People With Transplantsmentioning
confidence: 99%
“…[7][8][9] The second part of the Hopkins study showed slightly more promise after the second dose of the vaccine. 4 We still need more clinical data, but how quickly will it arrive?…”
Section: A Call For Research Shared Decision-making and Empowering Patients With Knowledgementioning
confidence: 99%